Achieving photocatalytic hydrogen production from alkaline solution upon a designed mesoporous TiO2–Ni hybrid employing commonly used paper as a sacrificial electron donor. Issue 11 (7th September 2018) - Wei, Yi; Xiong, Jinyan; Li, Weijie; Kollarigowda, Ravichandran H.; Cheng, Gang
Abstract : Photocatalytic hydrogen evolution from water splitting, using paper as an electron donor, was achieved upon use of a hybrid photocatalyst of mesoporous TiO2 decorated with Ni nanoparticles. Abstract : Photocatalytic hydrogen evolution from water splitting, using paper as an electron donor, was achieved upon the use of a hybrid photocatalyst of mesoporous TiO2 decorated with Ni nanoparticles. Through the involvement of a Ni cocatalyst, the separation and migration of photo-generated electrons in TiO2 –Ni hybrids were significantly enhanced. The soluble paper in alkaline solution played the role of a sacrificial electron donor by reacting with hydroxyl radicals generated from hole oxidation with OH − . These findings provide an inexpensive route to drive aqueous proton reduction to hydrogen through waste biomass oxidation.